COMPARATIVE STUDY OF MENTAL TOUGHNESS OF INDIVIDUAL SPORTS AND TEAM GAME PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
To analyse the Psychological component i.e. mental toughness between team game and Individual sports of Haryana sportspersons and also compare it. This was a cross-sectional and experiment study. Mental toughness level was assessed of 500 subjects (250 males and 250 females) aged 17–28 years from different colleges and Universities of Haryana. Personal styles and performance questionnaire was used to collect the data. The results of the study showed that significant difference in mean values of male players of team games and Individual sports male in mental toughness was found and our hypothesis was accepted. The results of the study also showed that significant difference not found in mean values of female players of team games and Individual sports and our hypothesis was accepted.